The most-liked and least-liked television personalities and programs perceived by selected students of the San Miguel High School, Bulacan as related to some variables - Wichian Dechgoontong 1948-
This study aimed to look into the perceptions of selected high school students regarding their most-liked and least-liked television personalities and program references. It also determined the characteristics of the most-liked and least-liked television personalities as perceived by the respondents.